2020
DOI: 10.1038/s41598-020-60924-4
|View full text |Cite
|
Sign up to set email alerts
|

Proteinuria is Associated with Urinary Loss of Cubilin and Vitamin D-Binding Protein in Patients with Preeclampsia

Abstract: Women with preeclampsia (PE) form a vulnerable group for vitamin D3 deficiency. Reabsorption of vitamin D3 occurs in the proximal tubule after being endocytosed in combination with DBP (vitamin D binding protein) by the megalin/cubilin receptor. Because proteinuria promotes tubule injury and dysfunction, we hypothesized that the proteinuria present in pe could promote the loss of these components into the urine. Twenty preeclamptic patients and ten normal pregnant women with a gestational age greater than 20 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 20 publications
2
8
0
Order By: Relevance
“…They found that the increased oxidative stress correlated with a downregulated expression of certain proteins including VDBP, suggesting that increased oxidative stress may be responsible for the altered concentration of VDBP and vitamin D metabolism evidenced in the placentae of women with pre-eclampsia [89]. Moreover, pregnancies complicated by pre-eclampsia with proteinuria have been shown to result in a greater urinary loss of VDBP compared to non-proteinuric pre-eclampsia or normotensive pregnancies, suggesting a possible disruption to the vitamin D metabolism and function through reduced VDBP [123].…”
Section: Vdbp and Preeclampsiamentioning
confidence: 99%
“…They found that the increased oxidative stress correlated with a downregulated expression of certain proteins including VDBP, suggesting that increased oxidative stress may be responsible for the altered concentration of VDBP and vitamin D metabolism evidenced in the placentae of women with pre-eclampsia [89]. Moreover, pregnancies complicated by pre-eclampsia with proteinuria have been shown to result in a greater urinary loss of VDBP compared to non-proteinuric pre-eclampsia or normotensive pregnancies, suggesting a possible disruption to the vitamin D metabolism and function through reduced VDBP [123].…”
Section: Vdbp and Preeclampsiamentioning
confidence: 99%
“…As a result, the authors were able to prove an association between preeclampsia and vitamin D3 deficiency, because proteinuria causes the loss of proteins responsible for reabsorption of vitamin D3 by renal tubules. In combination with other factors, proteinuria can accelerate vitamin D3 deficiency in preeclampsia [66]. Therefore, both the symptoms of preeclampsia, arterial hypertension and proteinuria are both associated with vitamin D deficiency.…”
Section: Impact Of Proteinuria On Vitamin D Concentrations During Pre...mentioning
confidence: 99%
“…As a result, the authors were able to prove an association between preeclampsia and 25(OH)D deficiency, because proteinuria causes the loss of proteins responsible for the reabsorption of 25(OH)D by renal tubules. In combination with other factors, proteinuria can accelerate 25(OH)D deficiency in preeclampsia [ 67 ]. Therefore, both the symptoms of preeclampsia, arterial hypertension and proteinuria, are associated with 25(OH)D deficiency.…”
Section: Impact Of Proteinuria On 25(oh)d Concentrations During Pregn...mentioning
confidence: 99%